Observation of the strange sea in the proton via inclusive phi-meson production in neutral current deep inelastic scattering at HERA - Chekanov, S; Krakauer, D; Magill, S; Musgrave, V; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Basile, M; Bellagamba, L; Boscherini, D; et al. (2003)
Inclusive φ(1020)-meson production in neutral current deep inelastic e+p scattering has been measured with the ZEUS detector at HERA using an integrated luminosity of 45 pb-1. The φ mesons were studied in the range 10 < Q2 < 100 GeV2, where Q2 is the virtuality of the exchanged photon, and in restricted kinematic regions in the transverse momentum, pT, pseudorapidity, η, and the scaled momentum in the Breit frame, xp. Monte Carlo models with the strangeness-suppression factor as determined by analyses of e+e- annihilation events overestimate the cross sections. A smaller value of the strangeness-suppression factor reduces the predicted cross sections, but fails to reproduce the shapes of the measured differential cross sections. High-momentum φ mesons in the current region of the Breit frame give the first direct evidence for the strange sea in the proton at low x. © 2002 Published by Elsevier Science B.V.